Hierarchical Porous Nitrogen‐Doped Carbon Modified with Nickel Nanoparticles for Selective Ultradeep Desulfurization. Issue 28 (24th July 2020) - Ganiyu, Saheed A.; Tanimu, Abdulkadir; Azeez, Musa O.; Alhooshani, Khalid
Abstract: We report herewith, a biomass derived carbon from groundnut shell (GN‐AC) treated with melamine to achieve nitrogen‐doped carbon (CN), followed by modification with nickel‐precursor by solid‐state impregnation to achieve reticulated nickel nanoparticles‐modified nitrogen‐doped carbon (Ni‐CN) adsorbent. Incorporation of heteroatoms and the subsequent loading of nickel nanoparticles on the porous carbon exhibits fast and remarkable adsorption capacity for dibenzothiophene. The sulfur removal efficiencies of CN and Ni‐CN are 40.49 and 44.77 mg‐S/g‐adsorbent, respectively, compared to 29.63 mg‐S/g achieved for bare carbon in 500 ppmw‐S. This excellent performance is attributed to synergy effect of nitrogen heteroatoms and nickel nanoparticles with improved surface chemistry and textural properties. The physical‐chemical properties of the adsorbents were characterized by Boehm titration, N2 ‐physisorption, FTIR, XRD, XPS, Raman, SEM and TEM. The kinetics and isotherms investigation of the adsorbents data fitted pseudo‐first order and Langmuir models, respectively. The Ni‐CN adsorbent also displays an excellent selectivity and regeneration potential for commercial viability. Abstract : Porous carbon doped with nitrogen was modified with nickel to prepare highly active and selective adsorbent for ultradeep desulfurization of dibenzothiophene. The carbon was synthesized from biomass precursor using groundnut‐shell activated with ZnCl2 under pyrolysis. Nitrogen and nickel were incorporated via solid state impregnation to prepare low‐cost adsorbent for desulfurization of fuel